Three-dimensional flow structures in X-shaped junctions: Effect of the Reynolds number and crossing angle - Correa, Pablo Germán (2019)
We study numerically the three-dimensional (3D) dynamics of two facing flows in an X-shaped junction of two circular channels crossing at an angle α. The distribution of the fluids in the junction and in the outlet channels is determined as a function of α and the Reynolds number Re. Our goal is to describe the different flow regimes in the junction and their dependence on α and Re. We also explore to which extent two-dimensional (2D) simulations are able to describe the flow within a 3D geometry. In the 3D case, at large Re?s (≳50) and α?s (≳60°), axial vorticity (i.e., parallel to the outlet axis) of magnitude increasing both with α and Re develops in the outlet channels and cannot be reproduced by 2D numerical simulations. At lower angles (α ≲ 60°), instead, a mean vorticity component perpendicular to the junction plane is present: both its magnitude and the number of the corresponding vortices (i.e., recirculation zones) increase as α decreases. These vortices appear in both 2D and 3D simulations but at different threshold values of α and Re. At very low Re?s (≲5) and α?s (∼15°), the flow structure in 3D simulations is nearly 2D but its quantitative characteristics differ from 2D simulations. As Re increases, this two-dimensionality disappears, while vortices due to flow separation appear in the outlet channels.